Vegetable Value Chain Survey in Ethiopia: Producer/Household Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This vegetable producer survey was a part of a large-scale vegetable value chain survey which was conducted to understand how the vegetable value chain is transforming in terms of adoption of modern inputs, productivity, quality, and demand for vegetables in Ethiopia. The survey was conducted among 810 farmers. Information was collected on household characteristics, income-generating activities, assets, and details on vegetable activities.